PERMASALAHAN PENUNTUTAN TERHADAP PELAKU PENYALAH GUNA NARKOTIKA DI WILAYAH HUKUM KEJAKSAAN NEGERI PADANG - Rikhi Benindo Maghaz (STIH Putri Maharaja, 2019)
In the case handling of narcotics abuse, the public prosecutor at the Padang District Attorney’s Office only proceed articles that had been suspected by the investigator, without proving accurately the status of the narcotics abuser. This research is aiming to understand the handling of narcotics abuse and its issues during the prosecution process at the Padang District Attorney’s Office. This research is using empirical normative research methodology. Based on the research, the public prosecutor at the Padang District Attorney’s Office did not precisely investigate and probe material evidence related to the status of the perpetrators of narcotics abuse. As a result, in indictment letter, the case of narcotics abuses always being overlaid with the harsher indictment articles, namely Article 111, 112, or 114 of Law Number 35 of 2009, which detention be applicable to the perpetrators. Supposing only a single indictment of article 127 is applied, the perpetrator of the narcotics abuse shall not be detained as stipulated in Article 21 paragraph (4) of KUHAP. This condition is clearly detrimental to the narcotics abuser, especially those people in addiction or victims of narcotics abuse, where they should be placed at the Rehabilitation Institute. Due to the absence of public prosecutor's meticulous attempt in probing material evidence related to the status of the perpetrators of narcotics abuse, it may cause false sentence declared by the judge.